Hispanics With Primary Biliary Cirrhosis Are More Likely to Have Features of Autoimmune Hepatitis and Reduced Response to Ursodeoxycholic Acid Than Non-Hispanics - Levy, Cynthia; Naik, Jahnavi; Giordano, Christin; Mandalia, Amar; O'Brien, Christopher; Bhamidimarri, Kalyan R.; Schiff, Eugene R.; Martin, Paul (Clinical gastroenterology and hepatology, 2014)
Primary biliary cirrhosis (PBC) is a cholestatic disease that predominantly affects middle-aged Caucasian women. Studies have suggested that PBC has a more aggressive course in individuals of Hispanic ancestry. We investigated the clinical presentation and progression of PBC in an ethnically diverse population. We performed a cross-sectional study, analyzing data from Hispanic (n = 70) and non-Hispanic patients (n = 134) with PBC seen at the University of Miami/Jackson Memorial Hospital from January 1, 2000, through December 31, 2011. We compared demographics, clinical presentation, response to therapy, and outcomes between the groups. Age at diagnosis, antimitochondrial antibody positivity, frequency of advanced histologic stage, use and dose of ursodeoxycholic acid (UDCA), and the presence of pruritus or fatigue were similar between groups. Hypothyroidism was less frequent among Hispanics (16% vs 29% in non-Hispanics; P = .04). Hispanic subjects were more likely to have overlap syndrome of PBC and autoimmune hepatitis than non-Hispanics (31% vs 13%; P = .002). After a median follow-up period of 3.65 years, a greater percentage of Hispanics had ascites (24% vs 12%; P = .03) and variceal bleeding (20% vs 7%; P = .01), although there were no differences in the number of deaths or liver transplants. Of 204 total patients, 180 received UDCA for at least 1 year. A lower proportion of Hispanic patients had a biochemical response to treatment (60% vs 88%; P < .0001). Independent predictors of poor biochemical response were younger age at diagnosis and Hispanic ethnicity. In a cross-sectional study, patients of Hispanic ethnicity with PBC had an increased prevalence of overlap syndrome, reduced response to UDCA treatment, and more frequent complications of portal hypertension than non-Hispanic patients.